2019
DOI: 10.1101/677898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in the intracranial volume from early adulthood to the sixth decade of life: A longitudinal study

Abstract: AbstractNormal brain-aging occurs at all structural levels. Excessive pathophysiological changes in the brain, beyond the normal one, are implicated in the etiology of brain disorders such as severe forms of the schizophrenia spectrum and dementia. To account for brain-aging in health and disease, it is critical to study the age-dependent trajectories of brain biomarkers at various levels and among different age groups.The intracranial volume (ICV) is a key bio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 86 publications
0
13
2
Order By: Relevance
“…More recent studies have confirmed greater ICV in males as well as changes in ICV throughout the lifespan (Caspi et al 2020; Mills et al 2016). ICV shows significant increases throughout childhood and adolescence (Mills et al 2016; Dong, Castellanos, et al 2020), followed by gradual increases in early adulthood until the fourth decade of life after which it begins to decrease (Caspi et al 2020). These changes in ICV parallel shifts in cortical expansion (Hill et al 2010), myelination (Grydeland et al 2019), structure-function coupling (Baum et al 2020), and functional maturation of association networks (Dong, Margulies, et al 2020) throughout the lifespan (Sydnor et al 2021).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…More recent studies have confirmed greater ICV in males as well as changes in ICV throughout the lifespan (Caspi et al 2020; Mills et al 2016). ICV shows significant increases throughout childhood and adolescence (Mills et al 2016; Dong, Castellanos, et al 2020), followed by gradual increases in early adulthood until the fourth decade of life after which it begins to decrease (Caspi et al 2020). These changes in ICV parallel shifts in cortical expansion (Hill et al 2010), myelination (Grydeland et al 2019), structure-function coupling (Baum et al 2020), and functional maturation of association networks (Dong, Margulies, et al 2020) throughout the lifespan (Sydnor et al 2021).…”
Section: Introductionmentioning
confidence: 84%
“…The volume of the cranium, typically referred to as intracranial volume (ICV) or estimated total intracranial volume, was historically thought to increase during development and remain stable throughout adulthood (Matsumae et al 1996), with larger volumes in males than in females throughout the lifespan (De Bellis et al 2001; Cosgrove, Mazure, and Staley 2007). More recent studies have confirmed greater ICV in males as well as changes in ICV throughout the lifespan (Caspi et al 2020; Mills et al 2016). ICV shows significant increases throughout childhood and adolescence (Mills et al 2016; Dong, Castellanos, et al 2020), followed by gradual increases in early adulthood until the fourth decade of life after which it begins to decrease (Caspi et al 2020).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations